2022
DOI: 10.1039/d2cc02470e
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive proton conduction in Zr-based metal–organic frameworks using the photothermal effect

Abstract: A highly stable and porous MOF [Zr2(H4TPPP)(OH/F)2]·xH2O (1) containing metal-free porphyrin-phosphonate ligand is reported. It shows high proton conductivity of 1.2 × 10-3 S·cm-1 at 25 °C and 95% RH,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…It is worth mentioning that porphyrin-phosphonate-based MOFs or CPs are still limited in number. They usually contain only one kind of ligand such as M–H 8 TPPP (M = Ni, Cu) or H 10 TPPP and show 3D framework structures. ,,, The only exception, as far as we are aware, is [(CH 3 ) 2 NH 2 ] 2 [Ni­(Cu–H 4 TPPP)] which has a 1D chain structure . Thus, compounds CoNi , NiNi , and CoCo are the second examples of metal porphyrin-tetraphosphonates showing a 1D chain structure.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is worth mentioning that porphyrin-phosphonate-based MOFs or CPs are still limited in number. They usually contain only one kind of ligand such as M–H 8 TPPP (M = Ni, Cu) or H 10 TPPP and show 3D framework structures. ,,, The only exception, as far as we are aware, is [(CH 3 ) 2 NH 2 ] 2 [Ni­(Cu–H 4 TPPP)] which has a 1D chain structure . Thus, compounds CoNi , NiNi , and CoCo are the second examples of metal porphyrin-tetraphosphonates showing a 1D chain structure.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we found that the absorption bands of a highly stable 3D Zr-MOF based on 5,10,15,20-tetrakis­( p -phenylphosphonic acid)-porphyrin (H 10 TPPP) approached ca. 1200 nm in the solid state . The significant red-shift of the absorption band is attributed to the rigid framework structure and the π–π interactions between the stacked porphyrin moieties in the structure .…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations